Simian Varicella Virus: Molecular Virology - Gray, Wayne L. (2010)
Simian varicella virus (SVV) is a primate herpesvirus that is closely related to varicella-zoster virus (VZV), the causative agent of varicella (chickenpox) and herpes zoster (shingles). Epizootics of simian varicella occur sporadically in facilities housing Old World monkeys. This review summarizes the molecular properties of SVV. The SVV and VZV genomes are similar in size, structure, and gene arrangement. The 124.5 kilobase pair (kbp) SVV genome includes a 104.7 kbp long (L) component covalently linked to a short (S) component which includes a 4.9 kbp unique short (US) segment flanked by 7.5 kbp inverted repeat sequences. SVV DNA encodes 69 distinct open reading frames (ORFs), three of which are duplicated within the viral inverted repeats. The viral genome is coordinately expressed and immediate early (IE), early, and late genes have been characterized. Genetic approaches have been developed to create SVV mutants, which will be used to study the role of SVV genes in viral pathogenesis, latency, and reactivation. In addition, SVV expressing foreign genes are being investigated as potential recombinant varicella vaccines.